Investigating the moderating role of knowledge: The relationship between auditor’s experience and ethical judgment - Hamzah Idris, Muhammad; Jamali, Hisnol; Sjahruddin, Herman (Advances in Social Sciences Research Journal, 2019)
Based on ethical judgment, we examine the Auditor experience and ethical judgment: Examining the moderating role of knowledge. We hypothesize that the auditor’s knowledge can be moderate the effect of auditor’s experience on ethical judgment. Our research hypothesis was tested in a survey of 97 government auditors in South Sulawesi (Indonesia). Variance-based SEM techniques (structural equation models) with employs WarpPLS 6.0 was used to verify the hypothesis. The results of the study show that the auditor’s knowledge acts as a quasi-moderator variable in explaining the relationship between auditor’s experience and ethical judgment.